Faktor yang Berhubungan dengan Penerimaan Sistem Pendaftaran Online Rumah Sakit - Wardani, Ana Kusuma; Rifai, Ahmad; Pitoyo, Achmad Zani (Politeknik Negeri Jember, 2025)
The online registration system has been implemented by many healthcare service providers, including Kanjuruhan Hospital, Malang Regency. This system aims to facilitate patient access to hospital registration from anywhere without the need for long waiting times. The objective of this study is to examine outpatient perceptions regarding the usefulness and ease of use of the online registration system and its impact on their acceptance of the system. This research adopts a quantitative analytical approach, focusing on outpatients using the online registration system. The study is based on the Technology Acceptance Model (TAM) with a cross-sectional approach. A total of 80 respondents were selected as the sample, and data were analyzed using the Spearman rank test. The findings indicate that the perceived usefulness variable in relation to user acceptance yielded a p-value of 0.000 < 0.05, and the perceived ease of use variable in relation to user acceptance also yielded a p-value of 0.000 < 0.05. These values demonstrate a correlation between the two variables, as the correlation values are lower than the significance level. The study concludes that user acceptance is significantly influenced by perceptions of usefulness and ease of use.